Regulation and Precariatisation of Working Life - Keller, Kurt Dauer; Keller, Hanne Dauer (European Journal of Social Science Education and Research, 2025)
The regulation of labour market attachment and working conditions now appears to be a thoroughly cultural and political issue, which is just as much a subjection to compulsory flexibility in association with the deregulation of collectively attained rights. Precarious working life is an age-old form of exploitation, expanding in our days to the academic fields of communication work and knowledge work. Sum and Jessop offer an approach to the theoretical understanding of this current epoch. However, their leaning on Foucault together with information science and systems science set a decisive limit to any phenomenological perspective of cultural and political experience – and thus hamper their project of outlining a cultural political economy. Still, Sum and Jessop’s important contribution to the notion of a cultural political economy must be recognized, not least when it comes to grasping the precariatisation of academic knowledge work and communication work.
Keywords: Regulation, precariatisation, working life